The Influence of The Financial Sector on The Success of Micro Enterprises in Surabaya City - Sri Nathasya Br Sitepu; Andri Wijanarko; Florencia Gunawan (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Micro enterprises in Indonesia are the largest in number compared to small and medium enterprises. Micro enterprises are spread throughout Indonesia, including Surabaya City. Micro enterprises will succeed if supported by good internal and external management of the business units. External factors come from outside the micro enterprise, while internal factors come from within the micro enterprise, one of which is the financial sector. Variables related to the financial sector include financial literacy, financial attitude, financial inclusion, business capital, and digital financial systems. Micro enterprises require research on financial variables to achieve success.Objective: This research aims to analyze the influence of financial factors, consisting of financial literacy, financial attitude, financial inclusion, business capital, and digital financial systems on the success of micro enterprises.Design/methodology/approach: This study is quantitative research using secondary data. The research involves 70 micro enterprises that received assistance from Ciputra University Surabaya. The sampling technique used is purposive sampling. Data analysis employs multiple linear regression analysis on micro enterprise data. The research location is in Surabaya City, corresponding to the location of micro enterprises that received assistance from Ciputra University Surabaya.Finding/result: The research findings show that the significance values for financial literacy and financial attitude variables are 0.00, which is less than 0.05 (α = 5%). This indicates that the financial literacy and financial attitude variables significantly influence the success of micro enterprises in Surabaya City. The significance values for financial inclusion, business capital, and digital financial systems are greater than 0.05 (α = 5%). This means that the success of micro enterprises assisted by Ciputra University Surabaya is not significantly influenced by the financial inclusion, business capital, and digital financial systems variables.Conclusion: Micro enterprises succeed when they enhance their knowledge of financial literacy and financial attitudes. This improvement can be achieved when micro enterprises participate in assistance and training from Ciputra University Surabaya.Originality/value (state of the art): This study finds that increasing financial literacy knowledge in micro enterprises has the greatest impact on their success. The role of educational institutions is crucial in enhancing skills and creating the success of micro enterprises. Micro enterprises should participate in training and assistance, especially in financial matters. Keywords: financial literacy, financial attitude, financial inclusion, business capital, micro enterprises